2021
DOI: 10.1039/d1gc02821a
|View full text |Cite
|
Sign up to set email alerts
|

Electro-oxidative C–H amination of heteroarenes with aniline derivatives via radical–radical cross coupling

Abstract: The selectively synthesis of C-2/C-3 aminated five-membered heteroarenes incorporated various functionalities with aniline derivatives in a sustainable way remains an unmet challenge. This protocol presents a practical protocol for C–H...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The adduct, 6 a , was detected using high‐resolution mass spectroscopy (HRMS), indicating the formation of the β‐dicarbonyl radical intermediate. In addition, adducts 6 b and 6 c were also detected using HRMS (Schemes 4b and 4c), which indicated that a nitrogen radical was generated and subsequently transformed into a carbon radical [11c,17] . Moreover, it should be noted that 6 d was obtained by slightly varying the reaction conditions (Scheme 4d).…”
Section: Methodsmentioning
confidence: 96%
“…The adduct, 6 a , was detected using high‐resolution mass spectroscopy (HRMS), indicating the formation of the β‐dicarbonyl radical intermediate. In addition, adducts 6 b and 6 c were also detected using HRMS (Schemes 4b and 4c), which indicated that a nitrogen radical was generated and subsequently transformed into a carbon radical [11c,17] . Moreover, it should be noted that 6 d was obtained by slightly varying the reaction conditions (Scheme 4d).…”
Section: Methodsmentioning
confidence: 96%
“…Given our previous work and above points, a series of sulfonamide derivatives containing propargyloxy group were synthesized by inverting sulfonamide with N ‐butyl‐4‐propargyloxybenzenesulfonamide as the lead compound, and a series of sulfonamide derivatives containing pyridine skeleton were designed by combination principle in this study ( Figure 1). In this article, a total of thirty‐seven compounds were designed and synthesized, among which compounds A5, A9 and C7‐C9 have been reported in the literature [25–28] . Subsequently, the insecticidal activities of the designed compounds were tested and their structure–activity relationships were carefully explored to provide new ideas for the design and synthesis of insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Following our consistent interest in developing practical and operationally simple synthetic methods to gain valuable organic synthons, we envisaged whether we could apply a stepwise electrochemical oxidation to achieve difunctionalization of gem -difluoroalkenes with different nucleophiles under metal-catalyst- and chemical-oxidant-free conditions (Scheme c). Meanwhile, organic electrochemical synthesis has been recognized as environmentally benign and a practical synthetic tool, and several seminal works for the electrochemical difunctionalization of alkenes have been demonstrated .…”
mentioning
confidence: 99%